2016
DOI: 10.1007/s10943-016-0305-9
|View full text |Cite|
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of Spiritual Well-Being Scale in Patients with Acute Myocardial Infarction

Abstract: The purpose of this study was to assess the psychometric properties of the Persian version of Spiritual Well-Being Scale (SWBS) in patients with acute myocardial infarction. A multisite, cross-sectional survey was employed to determine the instrument’s reliability (Cronbach’s α and construct reliability) and validity (face, content, and construct). Using systematic sampling of adult outpatients at primary care clinic sites in the Qazvin City, Iran (N = 300), it was found that the Cronbach’s alpha and construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Face, content, and structural validity of the spiritual well-being scale were approved in the study conducted by Soleimani et al to assess its psychometric properties among patients with acute myocardial infarction. Its reliability was also evaluated using internal consistency method, revealing Cronbach's alpha >0.8 [37].…”
Section: Data Measurementsmentioning
confidence: 99%
“…Face, content, and structural validity of the spiritual well-being scale were approved in the study conducted by Soleimani et al to assess its psychometric properties among patients with acute myocardial infarction. Its reliability was also evaluated using internal consistency method, revealing Cronbach's alpha >0.8 [37].…”
Section: Data Measurementsmentioning
confidence: 99%
“…ICC results were interpreted as follows: 0.0-0.2 is low, 0.21-0.40 is fair, 0.41-0.60 is moderate, 0.61-0.80 is substantial, and 0.81-1 is almost perfect [25] which indicate that, the Arabic MIDAS is reliable in all subscales and has homogeneity. This result is in accordance with that of a Farsi study which revealed that, the ICC ranged from 0.81 to 0.97 [20], Chinese-Mandarin study in which it was ranged from 0.74 to 0.94 [21].However the same result is contrasted with the result of the original English scale by Thompson, et al (2002) (0.34-0.84) [16], and two Turkish study done by Uysal, et al (2009) [24] and Uysal and Ozcan (2011) [23] in which ICC ranged between 0.27-0.74 and 0.41-0.86 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…One such study implies that spirituality, as a complex construct, includes existential and also religious dimensions (Hungelmann, Kenkel-Rossi, Klassen, & Stollenwerk, 1996). It refers to the affective experiences of positive feelings from the person's ability to understand the purpose in life -related to personal, communal, and transcendental aspects (Soleimani et al, 2017). Religious dimension as the transcendental aspect in the construct of spirituality can be determined as a person's qualification and his/her ability to control his/her feelings related to how he/she interprets and makes a reflection of his/her religious belief.…”
Section: Safa'at Ariful Hudha and Djemari Mardapimentioning
confidence: 99%